Investigation of the incidence of Salmonella spp. in the diarrhoeic syndrome of young ruminants - ZDRAGAS (Α. ΖΔΡΑΓΚΑΣ) A.; PETSAGA-TSIMPERI (Β. ΠΕΤΣΑΓΚΑ-ΤΣΙΜΠΕΡΗ) V.; TSAKOS (Π. ΤΣΑΚΟΣ) P. (Journal of the Hellenic Veterinary Medical Society, 2018)
The presence of Salmonella spp. in the diarrhoeic syndrome of 24 cases of calves, 36 cases of kids and 14 cases of lambs was investigated. Salmonella was isolated as the pathogenic agent from six herds of calves and four cases of kids. The identified species was Salmonella enteritidis in three herds of calves and two cases of kids. Salmonella typhimurium was identified in two herds of calves and one case of kids. Also, Salmonella abony and Salmonella cerro were identified in one case of calves and kids, respectively. Furthermore, Shigella hyodysenteriae was isolated from two cases of diarrhoeic syndrome in lambs. All the infected animals were characterized by persistent haemorrhagic diarrhoea and high mortality. The occurrence of Salmonella enteritidis in ruminants is probably an important point of the epidemiology of Salmonella spp. and may play a significant role in the public health.